FEATURES OF ACCOUNTING AND TAXATION OF ROYALTY: KEY ASPECTS - Novichenko , L.S.; Stoika , N.S.; Shchyrska , O.V. (The actual problems of regional economy development, 2020)
The article is directed features of accounting and taxation of royalty in Ukraine. Considered the definition of the economic concept of «royalty» in the field of accounting and taxation which contained in regulations. There is determined that the reflection in the accounting of royalty should be provided with appropriate documentation. Royalties, as an object of accounting, provides for the conclusion of a license contract, according to the contract the licensor gives the license permission to use the intellectual property on the terms specified in the contract. Тhere is established that the accounting of royalty is carried out by reflecting the accrued amount of royalties as part of the costs of the reporting period by functional purpose. The features of royalty accounting are systematized, the emphasis is on the importance of developing appropriate documentation for accounting of business transactions related to the calculation of royalty, reflection in the accounts and financial statements of the enterprise. There is determined that the features of royalty taxation are regulated by norms of the Tax Code of Ukraine applies to such taxes as VAT, income tax, single tax, personal income tax, military duty. Research of the features and key aspects of royalty taxation allowed to establish the procedure for taxation of transactions on accrual and payment of royalties of legal entities in different tax systems.